1939
DOI: 10.1136/bmj.1.4075.264
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Syphilis by Blood Transfusion

Abstract: DIRECT IN6UIt AL HERNIA THE BRI; MDCL ORA indirect inguinal hernia. At operation the condition conformed in every way to that in Case 1, and it was treated in the same manner, except that silk was used to repair the hole in the transversalis fascia, and a silk darning-repair made of the inguinal canal. His recovery was uninterrupted.-,/,rm oLE .. ', HtMIALlC 4 LDn INGWINAL -IOU01 A diagrammatic drawing of the condition described. No attempt has been made to illustrate the bladder that forms part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1941
1941
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Bereits in den 1950er-Jahren wurde beobachtet, dass Treponema pallidum durch die Transfusion von Blutprodukten übertragen werden kann [20]. Dabei sind diese Bakterien sehr temperaturempfindlich.…”
Section: Syphiliserkrankungenunclassified
“…Bereits in den 1950er-Jahren wurde beobachtet, dass Treponema pallidum durch die Transfusion von Blutprodukten übertragen werden kann [20]. Dabei sind diese Bakterien sehr temperaturempfindlich.…”
Section: Syphiliserkrankungenunclassified
“…By the 1930s, the only infectious diseases known to be transmitted by blood transfusion were malaria [ 15 ] and syphilis [ 16 ]. In these early reports, the infections in the donor were frequently undetected.…”
Section: Emergence Of Pathogen Transmission As a Risk For Recipients ...mentioning
confidence: 99%
“…Syphilis has been transmitted via contaminated blood transfusions, [8][9][10][11][12][13][14][15][16] which has prompted routine serologic screening by blood banks. However, experiments have demonstrated that Treponetna pallidurn does not survive more than a few days under present blood banking conditions.12.…”
mentioning
confidence: 99%